The impact of a pandemic as an example of a stressful event, on anxiety and related emotional disorders of NF1 patients compared to healthy children - Cohen, Rony; Aharoni, Sharon; Halevy, Ayelet; Genizi, Jacob (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic has significantly affected global mental health, with children being particularly vulnerable. This study examines the psychological repercussions of the pandemic by comparing the prevalence of anxiety in healthy children and in those with Neurofibromatosis Type 1 (NF1), a hereditary disorder characterized by diverse clinical manifestations, including cognitive and behavioral challenges. The uncertainties of the pandemic may have influenced anxiety levels differently in these two populations.ResultsA cross-sectional survey of 52 parents revealed that, although not statistically significant, more children with NF1 reported generalized anxiety and social phobia compared with their healthy peers. Conversely, healthy children tended to report more symptoms of somatization disorder, although this difference was not significant. Parent-reported scores showed a significant association between NF1 and separation anxiety disorder.DiscussionThe findings suggest that the pandemic may have exacerbated pre-existing emotional challenges in children with NF1, potentially due to disruptions in healthcare access and increased social isolation. In contrast, typically developing children may have experienced stressors related to remote learning and social distancing. These results underscore the importance of tailored interventions and support for children with NF1 to address their specific emotional needs during crises.ConclusionThis study highlights the distinct psychological impact of the COVID-19 pandemic on typically developing children and those with NF1. While further research is needed to clarify the long-term effects, the findings emphasize the necessity of early screening and targeted interventions to mitigate emotional distress in children with NF1 during times of crisis.